(untitled) (Journal of International Studies, 2025)
This study investigates regional variations in media framings of ISIS on X, identifying the key factors contributing to these differences. By analysing diverse perspectives and approaches adopted by media accounts, the research sheds light on how various factors shape media discourse on social media platforms. Data were collected from X using RStudio and the academictwitteR package. Network analysis was employed to identify key opinion leaders (KOLs) within each regional group, while framing analysis explored media variations through framing devices such as problem definition and causal interpretation. Findings reveal that Asian media primarily focus on local impacts, particularly the radicalization of Indonesian citizens by ISIS and egregious human rights abuses. Euro-Anglosphere media emphasize international involvement, highlighting violent acts and advocating for a coordinated global response. Middle Eastern media centre their framing on local events, including military engagements, cultural heritage destruction, and immediate regional consequences. These variations are influenced by factors such as geopolitical proximity, national context, domestic journalistic norms, and online netizen engagement patterns. Overall, this study provides valuable insights into the dynamics of media discourse on X concerning ISIS.